PERILAKU KONSUMEN TAKSI DI JAKARTA - Husein Umar (Jurnal Manajemen, 2011)
The purpose of this study is to reach opinions from taxi’s consumers in Jakarta area on service quality, consumer confidence, corporate image, customer satisfaction and brand equity. This study also examines the influence of service quality, consumer confidence and corporate image toward customer satisfaction and it’s impacts on brand equity of the companies. The object of this study is the taxi industry in Jakarta with the taxi usersin Jakarta as the unit of analysis. Data have been collected during August-September 2010 by using a questionnaire instrument distributed to 378 respondents based on judgemental sampling. The analytical tools employed in this study are SPSS software, SEM (Structural Equation Modeling), and LISREL software. This study concludes that the quality of service, consumer confidence, corporate image, customer satisfaction and brand equity of Taxi companies in Jakarta have been considered quite positive. The influence of service quality, trust and corporate image to the consumer satisfaction taxi companies as a whole has a positive and significant for all independent variables. Finally, the influence of service quality, and trust and corporate image on customer satisfaction toward brand equity of taxi firms is significantly positive.